1932
DOI: 10.1002/cber.19320650525
|View full text |Cite
|
Sign up to set email alerts
|

Über die Einwirkung von Halogen auf Aryl‐selen‐cyanide

Abstract: s12 B e h a g h e l , Seihert: L'ber die Einuirkung[Jahrg. 6.5Die obere Schicht enthalt den Kohlenwasserstoff C,,H,, und seine hoheren Homologen. Um eine groI3ere Menge davon zu erhalten, wurden IOO g Methyl-cyclopentan mit 45 g Aluminiumchlorid und 45 g Tetrachlorkohlenstoff 10 Tage verriihrt. Aus der oberen Schicht wurde die Fraktion 213 -215~ herausdestilliert und rnit Kohlendioxyd-Schnee zum Krystallisieren gebracht. Der aus Methylalkohol gereinigte Rorper zeigte den Schmp. 460 und envies sich durch seinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1941
1941
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Only a few of the many methods of preparation are listed: (4) Se02 + RH + AIXs -» RgSeX (88) (5) SeOCl2 + RH -> R2SeCl2 (1, 5, 127, 140) (6) RSeCN + Br2 -> RSeBr3 (6,14,16) The reactions of SeOCl2, Se2Cl2, and SeCl4 with olefins (17), phenols (127,140), phenol esters (1), and alkyl-aryl ketones (139) all yield selenonium compounds.…”
Section: Selenonium Compoundsmentioning
confidence: 99%
“…Only a few of the many methods of preparation are listed: (4) Se02 + RH + AIXs -» RgSeX (88) (5) SeOCl2 + RH -> R2SeCl2 (1, 5, 127, 140) (6) RSeCN + Br2 -> RSeBr3 (6,14,16) The reactions of SeOCl2, Se2Cl2, and SeCl4 with olefins (17), phenols (127,140), phenol esters (1), and alkyl-aryl ketones (139) all yield selenonium compounds.…”
Section: Selenonium Compoundsmentioning
confidence: 99%
“…(16) Allylbenzene. an anticipated secondary pyrolysis product, was also detected by NMR as a minor product, but was inseparable from c/s-dihydroindene 9 under the capillary GLC conditions utilized for product analysis. In a later run NMR analysis of the c/s-dihydroindene component after preparative GLC collection showed <10% contamination by allylbenzene.…”
Section: -200(1973) (15)mentioning
confidence: 98%
“…. (9) The measured parent ion (M+) mass is slightly beyond acceptable error limits due to interference by the 13C isotope peak of the intense (base) M+ - 1 ion; however, the flanking m/e 119 and 117 ions gave the correct accurate masses for the assigned structure. (10) After the studies reported in this paper were concluded our attention was directed to a report by T. Kumagai and T. Mukai [Chem.…”
mentioning
confidence: 95%
“…(1) The most extensive recorded studies of selenenic acids and their derivatives are those of Behaghel and coworkers (9,10,11,12,13). References to earlier investigations are cited in these papers.…”
Section: S Z \mentioning
confidence: 99%
“…It seems, however, that as a class the selenium derivatives are the more stable group. For example, the selenenyl halides are less readily hydrolyzed than the corresponding sulfenyl halides (12), and another illustration of this tendency toward greater stability is seen in the isolation of a larger number of selenenic acids than of sulfenic acids. As already noted in paragraph 4, however, it may be that the isolation of the selenenic acids, as in the case of 1-anthraquinonesulfenic acid, depends on structural features which are peculiar to those selenenic acids which permit of isolation.…”
Section: S Z \mentioning
confidence: 99%